PENGARUH IMPLEMENTASI PROGRAM PRO-SELF TERHADAP KUALITAS HIDUP PASIEN KEMOTERAPI DI IRNA 1 RSUP Dr. SARDJITO YOGYAKARTA - , KUNIARTI RACHMAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Chemotherapy affects the condition of cancer patients both physically, psychologically, socially and spiritually. PRO-SELF program is a psychoeducation program aimed for adult cancer patients to enhance patients' self care abilities to manage the side effects of chemotherapy and improve the quality of life of chemotherapy patients. Objective: Determine the effect of the PRO-SELF intervention program on quality of life of chemotherapy patients in IRNA 1 RSUP Dr. Sardjito. Method: The type and design of the study was pre experiment with one group pre test post test. The research was conducted in July-September 2013 in IRNA 1 RSUP Dr. Sardjito with 40 respondents as samples. Measurement of quality of life using the EORTC QLQ-C30 and analyzed using the Wilcoxon test with 95% level of significancy. Results: The results showed significant differences and clinical relevance (â¥ 10 points) between the median scores on a single item of sleep disturbance (16.66 points) and a single item of financial difficulties (16.67 points) between before and after the implementation of the PRO-SELF program. Conclusion: There was a significant influence of the quality of life and clinical relevance on a single item of sleep disturbance and a single item of financial difficulties between before and after the implementation of the PRO-SELF program.